Latihan Napas Dalam terhadap Peningkatan Arus Puncak Ekspirasi (Ape) Pasien Asma Di Balai Kesehatan Paru Masyarakat Kota Pekalongan - Dian Kartikasari; Nuniek Nizmah Fajriyah (Universitas Muhammadiyah Klaten, 2019)
Asthma is a condition that causes inflammation of the airway. Management of asthma in addition to pharmacological also with non-pharmacological, such as breathing exercises that can improve the lung function of asthma patients. The purpose of this study is to study breathing exercises to increase the peak flow of exhalation (APE) in asthma patients. This study uses a true experiment-interpretation-posttest method with a control group. The number of studies was 20 people who were divided into 2 groups: 10 intervention groups and 10 control groups. APE measurements use Philips respironic peak flow meters. Data were analyzed with the Mann-Whitney test. The results of research related to the increase in APE of asthmatic patients. It is expected that nurses apply deep breathing exercises as an independent nursing intervention for asthma patients. Further researchers can conduct a breathing exercise research in asthma patients by using an analytical tool using a spirometer